2010 IEEE Sixth International Conference on E-Science 2010
DOI: 10.1109/escience.2010.51
|View full text |Cite
|
Sign up to set email alerts
|

Tracking and Sketching Distributed Data Provenance

Abstract: Abstract-Current provenance collection systems typically gather metadata on remote hosts and submit it to a central server. In contrast, several data-intensive scientific applications require a decentralized architecture in which each host maintains an authoritative local repository of the provenance metadata gathered on that host. The latter approach allows the system to handle the large amounts of metadata generated when auditing occurs at fine granularity, and allows users to retain control over their prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Some SWf systems opt to rely on distributed file-systems that partition the metadata and store it at each node (e.g. [21], [32]), in a shared-nothing architecture, as a first step towards complete geographical distribution. Hashing is the most common technique for uniform partitioning: it consists of assigning metadata to nodes based on a hash of a file identifier.…”
Section: Related Workmentioning
confidence: 99%
“…Some SWf systems opt to rely on distributed file-systems that partition the metadata and store it at each node (e.g. [21], [32]), in a shared-nothing architecture, as a first step towards complete geographical distribution. Hashing is the most common technique for uniform partitioning: it consists of assigning metadata to nodes based on a hash of a file identifier.…”
Section: Related Workmentioning
confidence: 99%
“…It is shown that the proposed approach works for the Network File System [190]. Further research extends the collection of provenance metadata to distributed systems [66,130], distributed enterprise service buses [4] and cloud services [154,155,223]. In particular, [154,155] integrate provenance into the Amazon Simple Storage Service (S3).…”
Section: Cross-system Data Flow Tracking and Policy Propagation 161mentioning
confidence: 99%
“…Some workflow systems opt to rely on distributed file-systems that partition the metadata and store it at each node (e.g. [31], [32]), in a sharednothing architecture, as a first step towards complete geographical distribution. Hashing is the most common technique for uniform partitioning: it consists of assigning metadata to nodes based on a hash of a file identifier.…”
Section: Related Workmentioning
confidence: 99%